ProgClust: A progressive clustering method to identify cell populations - Li, Han; Wang, Ying; Lai, Yongxuan; Zeng, Feng; Yang, Fan (Frontiers in Genetics, 2023)
Identifying different types of cells in scRNA-seq data is a critical task in single-cell data analysis. In this paper, we propose a method called ProgClust for the decomposition of cell populations and detection of rare cells. ProgClust represents the single-cell data with clustering trees where a progressive searching method is designed to select cell population-specific genes and cluster cells. The obtained trees reveal the structure of both abundant cell populations and rare cell populations. Additionally, it can automatically determine the number of clusters. Experimental results show that Progclust can accurately identify the cell populations while it outperforms baseline methods.